The Development of Early Childhood Naturalist Intelligence through Environmental Education - Priadi, Agus; Fatria, Erian (JURNAL PENDIDIKAN USIA DINI, 2024)
Environmental education exists as a solution to improving the intelligence of early childhood naturalists, but its implementation is often forgotten or only as a hidden curriculum. The purpose of this study is to provide information related to the implementation of environmental education for early childhood to improve the intelligence of early childhood naturalists. The research method used in this study is a qualitative method presented in the form of an in-depth literature review. Literature study efforts are carried out by reading, observing, recognizing, and describing to analyze reading material in the form of related literature as a reference source. The result of this study is that the use of instructional strategies for gardening activities and creative game-based environmental learning can be considered to improve the intelligence of early childhood naturalists. In addition, it was also found that the material often used by educators to improve naturalist intelligence is the introduction of animals and plants. The trend of measuring the intelligence of early childhood naturalists uses many observation sheets, but it is also recommended to use research instruments that have been standardized or published in reputable scientific articles to obtain valid and reliable data. Keywords: environmental education, early childhood, naturalist intelligence References: Adawiyah, A. S. R., &; Dewinggih, T. (2021). Environmental Education in Early Childhood through the provision of trash cans and simulation methods. Proceedings UIN Sunan Gunung Djati Bandung, 1(November), 12–23. https://proceedings.uinsgd.ac.id/index.php/Proceedings Adawiyah, R., Rohyana, F., &; Ashari, M. A. (2019). Development of Naturalist Intelligence through Science-based Project Methods at TK Titipan ilahii rencoong Kelayu Jorong. CARE Journal, 7(1), 1–6. https://core.ac.uk/download/pdf/229499766.pdf Agustiana, M. (2021). Efforts to Improve Early Childhood Naturalistic Intelligence of 5-6 Years through Farming Activities at Tk PGRI Bandar Lampung [Raden Intan State Islamic University Lampung]. http://repository.radenintan.ac.id/15122/ Amini, R., &; Munandar, A. (2014). The influence of the outdoor-based environmental education learning model on mastery of the concept of environmental education for prospective elementary school teachers. Journal of Educational Research, 11(1), 14–21. http://www.jurnal.upi.edu/file/3_risda.pdf Anggraini, D. (2017). Improve the naturalist intelligence of children aged 5-6 years through plant exploration. Yaa Bunayya: Journal of Early Childhood Education, 1(2), 137–146. https://doi.org/https://doi.org/10.24853/yby.1.2.137-146 Aprilianti, R., &; Septiani, S. (2021). Improve the naturalist intelligence of children aged 5-6 years through a scientific approach. Golden Age Journal, Hamzanwadi University, 5(02), 393–407. https://doi.org/https://doi.org/10.29408/jga.v5i02.3962 Ardoin, N. M., &; Bowers, A. W. (2020). Early childhood environmental education: A systematic review of the research literature. Educational Research Review, 31(November 2019), 100353. https://doi.org/10.1016/j.edurev.2020.100353 Asih, S., &; Susanto, A. (2017). Increasing naturalist intelligence in children aged 5-6 years through learning models in natural material centers. Yaa Bunayya : Journal of Early Childhood Education, 1(1), 33–38. https://doi.org/https://doi.org/10.24853/yby.1.1.33-38 Chandrawati, T. (2021). ECCE teachers' understanding of environmental literacy is related to environmental education. Proceedings of Covid 19 Era Integrative Holistic Early Childhood Development, September, 125–130. https://ejurnal.pps.ung.ac.id/index.php/paudhi/article/view/897 Cinantya, C., &; Maimunah. (2022). Science Learning Based on Creative Play Activities in Wetland Environments to Develop Early Childhood Naturalistic Intelligence. Journal of Early Childhood Education Undiksha, 10(3), 449–456. https://doi.org/https://doi.org/10.23887/paud.v10i3.52560 Creswell W., J. (2013). Research Design Qualitative, Quantitative, and Mixed Approaches. Learning Library. Destarani, A., &; Sari, R. N. (2021). Naturalist Intelligence in PAUD SPS An-Nabat Class A. Journal of Madrasah Ibtidaiyah Teacher Education, 01(01), 1–6. https://doi.org/https://doi.org/10.54892/jpgmi.v1i1.127 Devi Artanti, G., Fidesrinur, F., &; Garzia, M. (2022). Stunting and Factors Affecting Toddlers in Indonesia. JPUD - Journal of Early Childhood Education, 16(1), 172–185. https://doi.org/10.21009/jpud.161.12 Djoehaeni, H. (2014). Learning Model of Environmental Education in Early Childhood Education. Edutech, 13(1), 1. https://doi.org/10.17509/edutech.v13i1.3216 Dwikayani, Y. (2015). IMPROVE CHILDREN'S NATURALIST INTELLIGENCE THROUGH GARDENING ACTIVITIES. Growth and Development : A Study of ECCE Theory and Learning, 5(01). https://doi.org/https://doi.org/10.36706/jtk.v5i1.8202 Ekayanti, Y. (2014). Developing naturalist intelligence about the preschool environment of children aged 5-6 years Tk Lkia III Pontianak. Journal of Equatorial Education and Learning, 3(3), 1–13. https://doi.org/https://dx.doi.org/10.26418/jppk.v3i3.5003 Fajrin, L. P. (2020). Environmental Education in Raudhatul Athfal. Journal of Tunas Siliwangi, 6(2), 71–77. https://doi.org/https://doi.org/10.22460/ts.v6i2p71-77.2080 Fajrin, L. P., &; Alwiyah, N. (2023). Implementation of Naturalist Intelligence Development in Early Childhood Aisyiyah Kindergarten Kartasura Branch. Journal of Shoots, 9(1), 8–16. https://doi.org/https://doi.org/10.22460/ts.v9i1.3387 Fang, W.-T., Hassan, A., &; LePage, B. A. (2022). The Living Environmental Education. Springer Nature. https://doi.org/10.1007/978-981-19-4234-1 Fatria, E. (2023). Differences in student knowledge about the health of public places and tourism using project based learning strategies and strategies. Human Care Journal, 8(3), 481–495. https://doi.org/https://dx.doi.org/10.32883/hcj.v8i3.2634 Fatria, E., Priadi, A., Artanti, G. D., &; Alhamda, S. (2024). Utilizing the Geoeco-Book Learning Package to Improve Eco-Literacy of Z Generation Students in Elementary Schools. GeoEco, 10(1), 39–53. https://doi.org/https://doi.org/10.20961/ge.v10i1.82151 Fatria, E., Putrawan, I. M., &; Artanti, G. D. (2019). Environment and commitment, locus of control and intention to act. Indian Journal of Public Health Research and Development, 10(9), 1781–1785. https://doi.org/10.5958/0976-5506.2019.02711.6 Fatria, E., Rahmat Suwandi SN, F., &; Fadhani, M. (2023). Socialization of education in nursing to improve interpersonal intelligence for students. Empowering Society Journal, 4(2), 125–139. https://ojs.fdk.ac.id/index.php/ESJ/article/view/2597/pdf Firdausyi, A. N., Noormawanti, N., &; Marlisa, L. (2022). Implementation of naturalist intelligence in children in the learning theme "I Love Indonesia." SNPPM-4 (National Seminar on Research and Community Service) in 2022 Universitas Muhammadiyah Metro, 4, 69–75. https://prosiding.ummetro.ac.id/index.php/snppm/article/view/62%0Ahttps://prosiding.ummetro.ac.id/index.php/snppm/article/download/62/61 Fuaida, R., Sari, I. K., &; Fitriani, F. (2023). Increase naturalist intelligence through science games in group B children of Al-Ikhlas Lamlhom kindergartenIncreasing naturalist intelligence through science games in group B children of Al-Ikhlas Lamlhom Kindergarten. Student Scientific Journal, 4(1), 1–14. https://jim.bbg.ac.id/pendidikan/article/view/935 Gumitri, A., &; Suryana, D. (2022). Stimulation of Naturalist Intelligence of Children Aged 5-6 Years through Life Science Activities. Journal of Obsession : Journal of Early Childhood Education, 6(4), 3391–3398. https://doi.org/10.31004/obsesi.v6i4.2334 Hadjichambis, A. C., &; Paraskeva-Hadjichambi, D. (2020). Education for Environmental Citizenship: The Pedagogical Approach. https://doi.org/10.1007/978-3-030-20249-1_15 Hasanah, N., Harmawati, D., Riyana, M., &; Usman, A. N. (2019). Improve naturalist intelligence of early childhood through gardening activities in group children a Merauke State Pembina Kindergarten. IOP Conference Series: Earth and Environmental Science, 343(1). https://doi.org/10.1088/1755-1315/343/1/012186 Hendriani, I., Adjie, N., &; Putri, S. U. (2023). Application of learning with an environmental approach to improve the intelligence of early childhood naturalists. Proceedings of PGPAUD UPI National Seminar Purwakarta Campus,2(1), 112–117. http://proceedings.upi.edu/index.php/semnaspgpaudpwk/article/view/2549%0Ahttp://proceedings.upi.edu/index.php/semnaspgpaudpwk/article/download/2549/2337 Hidayah, V. N., &; Baedowi, F. S. (2020). The role of PLH (Environmental Education) SMAN 3 Klaten New Normal Era: Planting from school to home. Environmental Education and Sustainable Development, 21(2), 1–12. https://doi.org/https://doi.org/10.21009/PLPB.212.01 Indrayani, D. P. (2021). Developing Children's Naturalistic Intelligence through Gardening Activities at Sukarame Group B Lotus Kindergarten Bandar Lampung for the 2020/2021 Academic Year [Raden Intan State Islamic University Lampung]. http://repository.radenintan.ac.id/15351/ Ismail, A. (2018). Development of Early Childhood Naturalist Intelligence Instruments in East Luwu Regency, South Sulawesi Province. Journal of Educational Evaluation, 9(1), 16–29. https://doi.org/doi.org/10.21009/JEP.091.03 Ismail, M. J. (2021). Character education cares for the environment and maintains cleanliness in schools. The Old Teacher : Journal of Education and Learning, 4(1), 59–68. https://doi.org/10.31970/gurutua.v4i1.67 Jufri, J., La Fua, J., &; Nurlila, R. U. (2019). Environmental Education at Public Elementary School 1 Baruga Kendari City. . . Al-TA'DIB: Journal of Educational Studies, 11(2), 164–181. https://ejournal.iainkendari.ac.id/index.php/al-tadib/article/view/1133 Juniarti, Y. (2015). Increasing naturalist intelligence through field trip methods. Early Childhood Education, 9(2), 272. https://doi.org/https://doi.org/10.21009/JPUD.092.05 Khan, R. I. (2022). Stimulation of early childhood naturalist (nature-smart) intelligence with an exploration approach to the natural environment. Proceedings of OPPSI National Seminar 2022, 62–69. https://publishing.oppsi.or.id/index.php/SN/article/view/9 Latifah, C. N., &; Prasetyo, I. (2019). Effectiveness of Educational Game for the Intelligence of Early Childhood Naturalist. 296(Icsie 2018), 310–314. https://doi.org/10.2991/icsie-18.2019.56 Marlyana, A. V. (2023). Field trip method (field trip) group B at the Faculty of Tarbiyah and Teacher Training in June 2023. Kiai Haji State Islamic UniversityACHMAD sIDDIQ. Martuti, N. K. T., Rahayuningsih, M., Zaka, M. N. H. F., & Arifin, M. S. (2022). ENVIRONMENTAL EDUCATION FOR CHILDREN IN MOUNTAIN FOREST BUFFER VILLAGE (Case Study: Ngesrepbalong Village, Limbangan District, Kendal Regency). Proceedings of Science XII National Seminar "PISA Through Future Science for an Environmentally Friendly Generation," 30–39. https://proceeding.unnes.ac.id/index.php/snipa/article/view/1334 Milin, S., Fadillah, F., &; Halida, H. (2014). Increased Intelligence of Naturalists Aged 5-6 Years in Pembina State Kindergarten. Journal of Equatorial Education and Learning, 3(8), 1–12. https://doi.org/https://dx.doi.org/10.26418/jppk.v3i8.6067 Mulyatno, C. B. (2022). Environmental Education from an Early Age in the Perspective of Y.B Mangunwijaya's Liberation Theology. Journal of Obsession : Journal of Early Childhood Education, 6(5), 4099–4110. https://doi.org/10.31004/obsesi.v6i5.2570 Nurdiansyah, E., &; Komalasari, K. (2023). Forming Ecological Citizenship through Community Activity-based Environmental Education. Environmental Education and Sustainable Development, 24(01), 1–12. https://doi.org/https://doi.org/10.21009/PLPB.212.01 Nurwati, R. (2020). Increasing naturalist intelligence through planting vegetable seeds for children aged 5-6 years at Permata Genting Boyolali Kindergarten. Semarang State University. Ultimate, C. B. (2015). Efforts to Improve Naturalist Intelligence through Traditional Market Games [Yogyakarta State University]. https://eprints.uny.ac.id/26707/1/SKRIPSI CHOIRUNNISA%27 BUDI PAMUNGKAS.pdf Pelima, J. N. (2014). Environmental Education with Outbound Method for Early Childhood: Literature Review. Journal of Academia, 1(2), 19–32. https://doi.org/http://dx.doi.org/10.31227/osf.io/ekzd3 Prezylia, Z., Sasongko, R. N., &; Ardina, M. (2021). Teachers' efforts in improving naturalist intelligence in PAUD IT Nur' A thifah Pasar Manna, South Bengkulu Regency. ECCE PEN Journal, 2(1), 33–40. https://doi.org/https://doi.org/10.33369/penapaud.v2i1.14843 Primahesa, A., Sajidan, S., & Ramli, M. (2023). Improving higher order thinking skills in high school biology: A systematic review. Biosphere: Journal of Biological Education, 16(1), 206–218. https://doi.org/https://doi.org/10.21009/biosferjpb.26724 Priyatna, A., Meilinawati, L., &; Subekti, M. (2017). Introduction of environmentally friendly lifestyles for mothers and children at Paud Siti Fatimah, Cirebon City. Journal of Community Service, 1(6), 348–351. http://jurnal.unpad.ac.id/pkm/article/view/16427 Rahmatunnisa, S. &, &; Halimah, S. (2018). Efforts to improve the naturalist intelligence of children aged 4-5 years through playing sand. Yaa Bunayya : Journal of Early Childhood Education, 2(1), 67–82. https://doi.org/https://doi.org/10.24853/yby.2.1.67-82 Rahmawati, L. E. (2018). Efforts to Improve the Naturalist Intelligence of Children Aged 4-5 Years Through the Application of Outdoor Learning at PAUD Aisyiyah Kasih Ibu Dukun District, Magelang Regency [Semarang State University]. https://lib.unnes.ac.id/32410/ Rocmah, L. I. (2016). Increasing Naturalist Intelligence Through Messy Play for Children Aged 5-6 Years. Pedagogy : Journal of Education, 5(1), 47–56. https://doi.org/10.21070/pedagogia.v5i1.88 Rossa, V. O. (2014). Optimization of Early Childhood Naturalist Intelligence through Science Learning with Horta Puppet Media [University of Bengkulu]. https://core.ac.uk/download/pdf/35338424.pdf Safira, A. R., &; Wati, I. (2020). The importance of environmental education from an early age. JIEEC (Journal of Islamic Education for Early Childhood), 1(1), 21. https://doi.org/10.30587/jieec.v1i1.1592 Sari, A. P., Febrini, D., &; Wiwinda, W. (2023). Implementation of Outdoor Learning in Developing Early Childhood Naturalist Intelligence. Journal of Elementary School (JOES), 6(1), 126–133. https://doi.org/10.31539/joes.v6i1.6743 Saripudin, A. (2017). Naturalist intelligence development strategies in early childhood. AWLADY : Journal of Child Education, 3(1), 1–18. https://doi.org/10.24235/awlady.v3i1.1394 Suhartini, Y., &; Laela, A. (2018). Improving Early Childhood Natural Intelligence through Animal Recognition at TK Pelita Kota Bandung. Journal of Obsession : Journal of Early Childhood Education, 2(1), 43. https://doi.org/10.31004/obsesi.v2i1.6 Sukanti, S. (2021). Improving the Intelligence of Early Childhood Naturalists through Plant Maintenance Activities in Group B at RA Az-Zahra Galang [Universitas Pembangunan Panca Budi]. https://repository.pancabudi.ac.id/website/detail/21620/penelitian/meningkatkan-kecerdasan-naturalis-anak-usia-dini-melalui-kegiatan-pemeliharaan-tanaman-pada-kelompok-b-di-ra-azzahra-galang Sumitra, A., &; Panjaitan, M. (2019). Improving the Intelligence of Early Childhood Naturalists through the Field Trip Method. Paud Lectura: Journal of Early Childhood Education, 3(2), 1–9. https://doi.org/https://doi.org/10.31849/paud-lectura.v3i01.3342 Susmini, S., &; Sumiyati, S. (2019). Efforts to improve the naturalist intelligence of children aged 3-4 years through area-based creative play. Golden Age: Scientific Journal of Early Childhood Development, 3(1), 17–28. https://doi.org/10.14421/jga.2018.31-02 Syarofi, R., Ridwan, M., &; Abidin, R. (2023). Application of Corn Seed Pounding Game to Increase Naturalist Intelligence in Group B RA Miftahul Ulum Singogalih Tarik Sidoarjo. Proceedings of the Conference of Elementary Studies, 627–646. https://journal.um-surabaya.ac.id/index.php/Pro/article/view/19781 Ulfa, M. D. (2014). The influence of environmentally sound learning as a means of increasing naturalist intelligence in children aged 5-6 years at Pertiwi Kindergarten, Gunugpati District, Semarang. Early Childhood Education Papers (BELIA), 3(1), 38–46. https://doi.org/https://doi.org/10.15294/belia.v3i1.3419 Ulfah, M., &; Khoerunnisa, Y. (2018). The Effect of Using Inquiry Learning Strategies on Early Childhood Naturalist Intelligence in Majalengka Regency. Al-Athfal : Journal of Child Education, 4(1), 31–50. https://doi.org/10.14421/al-athfal.2018.41-03 Walidaini, S. (2021). Development of Naturalist Intelligence in Early Childhood through the Project Approach [Ar-Raniry State Islamic University]. https://repository.ar-raniry.ac.id/id/eprint/27604/ Widhiani, P., &; Imam, M. (2018). ENVIRONMENTAL HYGIENE EDUCATION GAME (CASE STUDY IN TK TARBIYATUL MUTAALIMIN CANGKO VILLAGE). INTI TALAFA : Journal of Informatics Engineering, 10(02), 11–19. https://doi.org/https://doi.org/10.32534/int.v10i2.1607 Widiawati, M. (2022). Analysis of the Application of Environmental Education in Elementary Schools. Radiant, 6(1), 181–186. https://doi.org/https://doi.org/10.52802/pancar.v6i1.333 Wijaya, I. K. W. B., & Dewi, P. A. S. (2021). Development of Early Childhood Naturalist Intelligence through the Unesco Environmental Education Model. Ideas: Educational, Social, and Cultural Journals, 7(3), 97. https://doi.org/10.32884/ideas.v7i3.449 Winangun, I. M. A. (2020). Introduction to Life Science for Early Childhood through flashcard media with local content. Widya Kumara:Journal of Early Childhood Education, 1(2), 80–89. http://stahnmpukuturan.ac.id/jurnal/index.php/JPAUD/article/view/934/804%0Ahttp://stahnmpukuturan.ac.id/jurnal/index.php/JPAUD/article/view/934 Yunisari, D., Amri, A., &; Fakhirah, F. (2016). Development of Children's Naturalist Intelligence in the Center for Natural Materials at PAUD Terpadu Aceh Besar. Scientific Journal of Early Childhood Education Students, 1(1), 11–18. https://jim.usk.ac.id/paud/article/view/363